Improving Students’ Vocabulary Mastery by Using Authentic Materials through Communicative Approach - Umar Umar; Irmayanti Irmayanti (Ethical Lingua: Journal of Language Teaching and Literature, 2017)
The research aimed at finding out whether or not using of authentic materials through communicative approach improves the vocabulary of the students. This applied a pre-experimental method. The population of the research was the second grades students of a state high school comprising four classes and one of which chosen as the sample by using purposive sampling. The sample consisted of thirty two. The data were collected by using vocabulary test that consisted 20 items. The proce4 of collecting data was presented in chronological order as pre-test given before treatment and then post-test was giving after treatment as students’ achievement. The data analysis showed that there was significant difference of the students’ vocabulary achievement after giving treatment by using authentic materials through communicative approach. It was proved by the mean score of pre-test was 5.97 and the mean of post-test was 7.82. The data was analyzed by using t-test was higher than t-table value. The value of t-test was 9, while t-table value was 1.695 at the 0.05 level significance. Based on the result above, the writer concludes that the use of authentic material through communicative approach improves the students’ vocabulary mastery.